Better Working Memory and Motor Inhibition in Children Who Delayed Gratification - Yu, Junhong; Kam, Chi-Ming; Lee, Tatia M. C. (Frontiers in Psychology, 2016)
Background: Despite the extensive research on delayed gratification over the past few decades, the neurocognitive processes that subserve delayed gratification remains unclear. As an exploratory step in studying these processes, the present study aims to describe the executive function profiles of children who were successful at delaying gratification and those who were not. =Methods: A total of 138 kindergarten students (65 males, 73 females; Mage = 44 months, SD= 3.5; age range= 37 to 53 months) were administered a delayed gratification task, a 1-back test, a Day/night Stroop test and a Go/no-go test. The outcome measures of these tests were then analyzed between groups using a Multivariate Analysis of Variance, and subsequently a Multivariate Analysis of Covariance incorporating age as a covariate. Results: Children who were successful in delaying gratification were significantly older and had significantly better outcomes in the 1-back test and go/no-go test. With the exception of the number of hits in the go/no-go test, all other group differences remained significant after controlling for age. Conclusion: Children who were successful in delaying gratification showed better working memory and motor inhibition relative to those who failed the delayed gratification task. The implications of these findings are discussed